Flossing Is Associated with Improved Oral Health in Older Adults. (August 2020) - Marchesan, J.T.; Byrd, K.M.; Moss, K.; Preisser, J.S.; Morelli, T.; Zandona, A.F.; Jiao, Y.; Beck, J.
The effect of preventive oral habits is largely unexplored in older individuals. The purpose of this study was to evaluate the associations between home use of flossing and prevalence of periodontal disease and caries in older adults. Five-year incident tooth loss was also evaluated. Data on 686 individuals ≥65 y-old from the Piedmont 65+ Dental Study were examined including: 1) interproximal clinical attachment level (iCAL), 2) interproximal probing depth (iPD), 3) numbers of caries, and 4) missing teeth. Flossing behavior was evaluated according to the Periodontal Profile Class (PPC) system. Five-year follow-up data ( n = 375) was evaluated for incident tooth loss. Dichotomous and categorical variables were analyzed using Pearson chi-square tests as well as covariate-adjusted Cochran-Mantel-Haenszel tests. Multiple linear regression compared clinical parameters based on flossing behavior. Elderly flossers had lower (mean, SE) %iCAL≥3 mm (38.2, 2.38 vs. 48.8, 1.56) and %iPD≥4 mm (8.70, 1.41 vs. 14.4, 0.93) compared to nonflossers ( P ≤ 0.005). Flossers showed less coronal caries compared to nonflossers ( P = 0.02). Baseline number of missing teeth (mean, SE) was 11.5 (0.35) in nonflossers compared to 8.6 (0.53) in flossers ( P < 0.0001). Regular dental visitors had lower oral disease levels compared to episodic dental users. The majority of flossers classified into PPC-Stage I (health) whereas nonflossers classified as PPC-Stages V, VI, and VII (disease). At the 5-y follow-up visit, the average tooth loss for flossers was ~1 tooth compared to ~4 teeth lost for nonflossers ( P < 0.0001). Among all teeth, molars showed the highest benefit (>40%) for flossing behavior ( P = 0.0005). In conclusion, the extent of oral disease for older individuals was significantly less in flossers than in nonflossers. Flossers showed less periodontal disease, fewer dental caries, and loss of fewer teeth over a 5-y period. These findings further support flossing as an important oral hygiene behavior to prevent oral disease progression in older adults.